2016
DOI: 10.1097/gme.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isolated vitamin D supplementation on the rate of falls and postural balance in postmenopausal women fallers

Abstract: In Brazilian postmenopausal women fallers, isolated vitamin D supplementation for 9 months resulted in a lower incidence of falls and improvement in postural balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 30 publications
1
46
0
2
Order By: Relevance
“…2019;11(1):3-5 EDITORIAL Muscle strength (especially proximal) can be modestly improved with vitamin D supplementation in the elderly with serum levels of 25OHD <12 ng/mL 16 . According to this concept, supplementation for 9 months with 1,000 IU of vitamin D 3 daily significantly decreased the first falls and the total of them in more than 50% of patients 13 .…”
Section: Quesada Gómez Jm Sosa Henríquez Mmentioning
confidence: 98%
See 2 more Smart Citations
“…2019;11(1):3-5 EDITORIAL Muscle strength (especially proximal) can be modestly improved with vitamin D supplementation in the elderly with serum levels of 25OHD <12 ng/mL 16 . According to this concept, supplementation for 9 months with 1,000 IU of vitamin D 3 daily significantly decreased the first falls and the total of them in more than 50% of patients 13 .…”
Section: Quesada Gómez Jm Sosa Henríquez Mmentioning
confidence: 98%
“…nuclear magnetic 11 . Some intervention studies show that administration of 800-1,000 IU of vitamin D 3 per day, or slightly more than its weekly equivalent, improves strength and balance in the elderly with vitamin D deficiency [12][13][14] .In addition to function, we have multiple observational studies that relate vitamin D deficiency with frailty and the incidence of falls. Thus, an analysis of 18 studies revealed an odds ratio (OR) of falls significantly greater than 1.23-1.44 for subjects with 25OHD concentrations below 10-20 ng/mL 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults supplemented with vitamin D demonstrate reduced risk of falls compared with non-vitamin D supplemented controls [2][3][4][5], though not all studies found a beneficial effect of supplementation on postural stability [6,7]. Muscle strength [5]; muscle function, including timed up-and-go [5,8] and chair stands [9]; balance [3][4][5]8]; reaction time [4] and gait [8] improved following vitamin D supplementation. However, positive studies often targeted vitamin D-deficient individuals [8] with a history of falls [3,4,9] and examined doses <4000 IU daily for <three years.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle strength [5]; muscle function, including timed up-and-go [5,8] and chair stands [9]; balance [3][4][5]8]; reaction time [4] and gait [8] improved following vitamin D supplementation. However, positive studies often targeted vitamin D-deficient individuals [8] with a history of falls [3,4,9] and examined doses <4000 IU daily for <three years. Conversely, randomized clinical vitamin D supplementation trials demonstrated no effect of 800 IU supplementation in older women with a history of falls [9] and a detrimental effect of 2800 IU supplementation in older vitamin D-insufficient women on muscle function and postural stability [6,7].…”
Section: Introductionmentioning
confidence: 99%